Технологічна модульна схема оброблення–дешифрування–геологічної інтерпретації матеріалів аерокосмічних знімань - Азімов, О.Т. (Геоінформатика, 2014)
Cхарактеризовано розроблену концептуальну узагальнену технологічну модульну схему оброблення, дешифрування і геологічної інтерпретації матеріалів аерокосмічних знімань у комплексі з даними геолого-геофізичних досліджень на підставі використання геоінформаційних технологій. Охарактеризована разработанная концептуальная обобщенная технологическая модульная схема обработки, дешифрирования и геологической интерпретации материалов аэрокосмических съемок в комплексе с данными геолого-геофизических исследований на основе использования геоинформационных технологий. The designed conceptual generic modular flowchart of transformation, decoding and geologic interpretation of remote sensing data in the complex with geological and geophysical data is characterised. The flowchart is based on geoinformation technologies application. As far as the novelty of elaboration this flowchart has the generalisable character relative to the previous analogues that allows conducting aero-space-geological studies in the multidimensional aspects instead of the restricted thematic one only. Furthermore the article shows the more complete version for the proper logical block scheme of remote and geological-geophysical data processing. In general, the flowchart consists of four main stages: 1) setting up a problem; 2) composing knowledge and data bases; 3) processing and analyses of data using the geographic information systems (GIS); 4) complex analysis and geological interpretation for the information integrated into the GIS. The flowchart is modular. Consequently its different parts (constituent elements) may be applied depending on the research level (global, regional, zonal or local scales) for the prospecting geological objects (i. e. disjunctive, petroleum promising and other ones), their complexity and completeness as well as the availability of remote sensing and geological-geophysical data. The flowchart is practically realized to study the features of the rupture dislocation of the Earth crust in the conditions of the different landscape-geological structure of Ukraine in frame of the scientific and applied problems of the use of subsurface resources and geoecology. The single modules of the flowchart are used to solve the problem of predicting the potential hydrocarbon traps.